2019
DOI: 10.1080/10826084.2019.1581221
|View full text |Cite
|
Sign up to set email alerts
|

Biased labels: An experimental study of language and stigma among individuals in recovery and health professionals

Abstract: Background: Labels such as "addict" and "substance abuser" have been found to elicit implicit and explicit stigma among the general public previously. The difference in the levels of this bias among individuals in recovery and those employed in the health profession has not yet been identified, however. The current study seeks to answer this question using measures of implicit bias. Methods: A subset sample (n = 299) from a previously completed study (n = 1,288) was selected for analysis. Mixed-model ANOVA tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 30 publications
1
39
1
1
Order By: Relevance
“…Recent research found that terms like "substance abusers" and "opioid addict" were associated with negative explicit bias (Ashford, Brown, & Curtis, 2018). Building upon those findings, the authors went on to find that stigmatizing terms have the potential to influence medical personnel and their perceptions of individuals with substance use disorders (Ashford, Brown, McDaniel, & Curtis, 2019). Subtle changes to language that reduce stigma might be especially impactful in this setting, as ER staff may be the first health professionals an overdose patient encounters.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research found that terms like "substance abusers" and "opioid addict" were associated with negative explicit bias (Ashford, Brown, & Curtis, 2018). Building upon those findings, the authors went on to find that stigmatizing terms have the potential to influence medical personnel and their perceptions of individuals with substance use disorders (Ashford, Brown, McDaniel, & Curtis, 2019). Subtle changes to language that reduce stigma might be especially impactful in this setting, as ER staff may be the first health professionals an overdose patient encounters.…”
Section: Discussionmentioning
confidence: 99%
“…To address this issue, the VHA and other national hospital authorities could publish specific guidance promoting evidence-based addictions hospital care 40 or create educational campaigns encouraging hospital-based OAT delivery. These initiatives would likely need to address provider knowledge gaps and addiction-related stigma, 20,41 describe pathways to OAT after discharge, and identify policies impeding care inside and outside the hospital-setting. 20 Future Research.…”
Section: Implications For Practice Research and Policymentioning
confidence: 99%
“…In fact, rigorous scientific investigations have now shown that certain common terms in the field used to describe individuals suffering from chronic drug-related impairment (e.g. 'substance abuser') may actually induce explicit and implicit cognitive biases that result in a perceived need for punishment rather than treatment [15][16][17]. Such research has made it difficult to trivialize and dismiss the terminology debate as merely 'semantics' or a linguistic preference for 'political correctness'.…”
Section: Introductionmentioning
confidence: 99%